PERAMALAN INDEKS HARGA PROPERTI RESIDENSIAL DI KOTA BANDUNG TAHUN 2023 - Savitri, Nurain Fatma; Nasrudin, Nasrudin (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2023)
Residential property or house is a basic need for humans. The increase in population causes the need for residential properties also increased. Because availability does not increase while demand increases, a shortage occurs which causes property prices, especially houses, to increase. Residential property is not only used as a necessity, but can also be used as an investment. So it is important for the holder policies and housing developers and the public to find out current and future conditions of the property sector, especially residential property which will come. Residential property is divided into three types based on area soil, namely small type, medium type, and large type. Property Price Index Residential is one of the economic indicators that provide information on residential property developments on a quarterly basis current and future quarters. IHPR data obtained from surveys Residential Property Prices conducted by Bank Indonesia. The aim of this research is to predict the value of the residential property price index in Bandung City. Applying the ARIMA forecasting method, this study found that the value It is predicted that the IHPR in the city of Bandung from the first quarter of 2023 to the fourth quarter of 2023 has increased, so it is known that the residential property sector in the City Bandung is moving in a positive direction.